2005
DOI: 10.1158/0008-5472.can-05-1277
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Promoter Methylation in Sporadic Breast Cancer Is Associated with Reduced BRCA1 Copy Number and Chromosome 17 Aneusomy

Abstract: To explore the molecular mechanisms for the similarities between inherited and noninherited forms of breast cancer, we tested the hypothesis that inactivation of BRCA1 by promoter hypermethylation is associated with reduced gene copy number and chromosome 17 aneusomy as observed in tumors from BRCA1 mutation carriers. Using a combination of methylation-specific PCR analysis and fluorescence in situ hybridization, we observed varying degrees of promoter methylation in 39 of 131 (29.8%) primary tumors. Despite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 33 publications
13
138
1
1
Order By: Relevance
“…All BRCAX cancers were studied previously for hypermethylation of the BRCA1 gene promoter and loss of heterozygosity; interestingly, the BRCAX samples that had basal-like phenotype showed biallelic inactivation of the BRCA1 gene (Honrado et al, 2007). This model of carcinogenesis in the BRCAX tumors is in agreement with the low level of BRCA1 mRNA expression reported in basal-like cancers (Staff et al, 2003;Wei et al, 2005;. On the other hand, the ERBB2 subtype comprised only of BRCAX tumors (four cases, B14%) (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…All BRCAX cancers were studied previously for hypermethylation of the BRCA1 gene promoter and loss of heterozygosity; interestingly, the BRCAX samples that had basal-like phenotype showed biallelic inactivation of the BRCA1 gene (Honrado et al, 2007). This model of carcinogenesis in the BRCAX tumors is in agreement with the low level of BRCA1 mRNA expression reported in basal-like cancers (Staff et al, 2003;Wei et al, 2005;. On the other hand, the ERBB2 subtype comprised only of BRCAX tumors (four cases, B14%) (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…Promoter hypermethylation of TS genes can serve as the first and/or the second hit in Knudson's model of tumor development. Approximately 20% of sporadic, in particular triple‐negative breast cancers33, 34 and a subset of ovarian cancers35 display BRCA1 promoter hypermethylation. It seems plausible to assume that the few hypermethylated alleles that were observed in some BC and control samples represent stochastic or environmentally induced somatic epimutations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BRCA1-associated breast cancers, which predominantly occur in premenopausal women, are more frequently of the ER-negative phenotype [7]. We previously demonstrated that inactivation of BRCA1 by promoter methylation is associated with reduced transcripts, decreased gene copy number and chromosome 17 aneusomy, as observed in tumors from BRCA1 mutation carriers [8]. Furthermore, an increasing number of studies have provided evidence linking disruption of Fanconi anemia/BRCA cascade in sporadic cancers [9].…”
Section: Introductionmentioning
confidence: 89%
“…Methylation specific PCR of BRCA1 was done using primer sequences reported previously for the methylated reaction [15] and unmethylated reaction [8]. FANCF methylation was analyzed as previously described [11].…”
Section: Brca1 and Fancf Promoter Methylation Analysesmentioning
confidence: 99%
See 1 more Smart Citation